2021
DOI: 10.5897/ajar2020.14897
|View full text |Cite
|
Sign up to set email alerts
|

A comparative economic analysis of aquaculture production systems in Southern Agricultural Zone of Cross River State, Nigeria

Abstract: This study was undertaken to determine the factors that influence the output of aquaculture production and the profitability of three production systems (concrete tank, earthen pond, and mobile tank) in Southern Agricultural Zone of Cross River State. A multi-stage stratified random sampling technique was used to select 140 farmers from three LGAs in the study area. Structured questionnaire was used for data acquisition. Descriptive and inferential statistics alongside budgeting techniques were used in data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…This, in turn, helps lower the overall production cost and increases profit margins. These findings align with the research conducted by Etuk et al (2021) who found out that the cost of production in earthen pond is relatively lower than in concrete tanks…”
Section: Water Sourcesupporting
confidence: 92%
“…This, in turn, helps lower the overall production cost and increases profit margins. These findings align with the research conducted by Etuk et al (2021) who found out that the cost of production in earthen pond is relatively lower than in concrete tanks…”
Section: Water Sourcesupporting
confidence: 92%
“…The zone is bounded by the River Niger on the west, the riverine Niger Delta on the south, the flat North central region to the north, and Cross River State on the east. The zone is located at Latitudes 4 o 30 1 and 7 o 30 1 North of the equator and longitudes 6 o 45 1 and 8 o 45 1 East of the Greenwich Meridian with a total land area of ten million, nine hundred and fifty-two thousand, four hundred hectares (10,952,400 ha). The zone contributes greatly to the Nigerian economy due to its endowment with arable land, oil and natural gas reserves along with the growing industrialised economy.…”
Section: Area Of the Studymentioning
confidence: 99%
“…Fish farming also moves the nation towards achieving its goals of food security generates employment and saves foreign exchange revenue through import substitution of fish and fish product (Esiobu and Onubuogu, 2014). As the human population increases and consequent protein demand, the over-exploitation of the natural fish resources has made aquaculture a major option to combat protein malnutrition in the country (Etuk et al, 2021). The demand for fish protein is about 2.7million MT and only 800,000 MT is produced locally.…”
Section: Introductionmentioning
confidence: 99%